DETERMINAN IMPLEMENTASI PENCATATAN KEUANGAN SEDERHANA PADA UMKM: PERAN PENGETAHUAN AKUNTANSI DASAR DAN PERILAKU PENGELOLAAN KEUANGAN - Yasri Tarawiru (Jurnal Ekonomi Ichsan Sidenreng Rappang, 2026)
This study examines the influence of basic accounting knowledge and financial management behavior on the implementation of simple financial recordkeeping among Micro, Small, and Medium Enterprises (MSMEs) in Parepare City. The research was motivated by the low quality of financial records among MSMEs, which often limits business decision-making, performance evaluation, and access to formal financing. A quantitative survey approach was employed involving 30 MSME owners selected through purposive sampling. Data were collected using a Likert-scale questionnaire and analyzed through validity, reliability, normality, and multiple linear regression tests using IBM SPSS Statistics 26. The results indicate that all research instruments were valid and reliable, with Cronbach’s Alpha values above 0.70. Regression analysis shows that basic accounting knowledge has a positive and significant effect on the implementation of simple financial recordkeeping (β = 0.374; p < 0.001), while financial management behavior also has a positive and significant effect (β = 0.310; p = 0.015). Simultaneously, both variables significantly influence financial recordkeeping practices (R² = 0.960). The findings highlight the importance of accounting literacy and sound financial management behavior in strengthening MSME financial administration and sustainability.